Teachers’ Creativity in Developing Speaking Skill of Junior High School Students in Yogyakarta - Endang Triningsih; Imam Ghozali (Journal of English Language and Pedagogy, 2018)
One of the two most determining factors in the teaching-learning process is teacher. Teacher backgrounds which affect the teaching-learning process cover wide aspects to include creativity. This paper reports a study to describe teachers’ creativity in developing the speaking skills of their students in Junior High Schools in Yogyakarta. The study belongs to qualitative research which data were collected from observation and interviews to four teachers selected from all English teachers in Yogyakarta teaching in both private and public schools based on their creativity in developing speaking skills. The observations were backed up with video-recording to catch detailed teacher-students interaction based on which the phenomenon understudy can be described. Follow-up interviews with teachers and students were conducted to help her in-depth understanding of the nature of creativity of the teachers, and thus triangulate the data for the study. Findings show that teachers’ creativity was exercised in encouraging students, questioning and teacher praising, using the learning material, developing learning activities, and Internet and Communication Technology. Further analysis found the teachers’ creativity was also employed in giving positive feedback and response, understanding students, mistake, and clear questions.